Multiple Internet of Robotic Things robots based on LiDAR and camera sensors. (8th April 2020) - Dai, Yanyan; Lee, Suk Gyu
A combination of Internet of Things and multiple robots with sensors has been an attractive research topic over the past years. This article proposes an Internet of Robotic Things system structure to monitor events, fuse sensor data, use local robots to determine a best action, and then act to control multiple mobile robots. The Internet of Robotic Things system includes two main layers: the host controller layer and the multiple robots layer. The controller layer communicates with the multiple robots layer by Wi-Fi module. The Internet of Robotic Things system helps finish five tasks: localizing robots, planning paths, avoiding obstacles, moving to waypoint stable, and creating a map. Based on depth data from depth camera and robot posture, a mapping algorithm is proposed to create map. Based on light detection and ranging sensor data and google cartographer, simultaneously localization and mapping (SLAM) is also processed in this article. The fuzzy sliding mode tracking control method is proposed for each robot to guarantee the robot stable moves. Simulation results show the effectiveness of the proposed algorithm and are used to compare with the experiment result. In the experiment, one host computer and two Kobuki mobile robots with light detection and ranging and depth camera sensors are integrated as an Internet of Robotic Things system. Two robots successfully localize themselves and avoid obstacles. The follower robot simultaneously builds a map.